2021
DOI: 10.3389/fncel.2021.640217
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP-Induced Alterations in Extracellular H+ Fluxes From Cultured Cortical and Hippocampal Astrocytes

Abstract: Small alterations in the level of extracellular H+ can profoundly alter neuronal activity throughout the nervous system. In this study, self-referencing H+-selective microelectrodes were used to examine extracellular H+ fluxes from individual astrocytes. Activation of astrocytes cultured from mouse hippocampus and rat cortex with extracellular ATP produced a pronounced increase in extracellular H+ flux. The ATP-elicited increase in H+ flux appeared to be independent of bicarbonate transport, as ATP increased H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 109 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…Extracellular ATP also elicits increases in extracellular H + fluxes from astrocytes cultured from mouse hippocampus and rat cortex (Choi et al, 2021). Cultured cells were identified as astrocytes by high levels of the intermediate filament protein glial fibrillary acidic protein (GFAP).…”
Section: H + Efflux From Glial Cells Elicited By Atpmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular ATP also elicits increases in extracellular H + fluxes from astrocytes cultured from mouse hippocampus and rat cortex (Choi et al, 2021). Cultured cells were identified as astrocytes by high levels of the intermediate filament protein glial fibrillary acidic protein (GFAP).…”
Section: H + Efflux From Glial Cells Elicited By Atpmentioning
confidence: 99%
“…A potent but commonly overlooked regulator of synaptic transmission is simple H + -that is, small changes in levels of extracellular acidity around sites of neurotransmitter release. Recent studies have shown that activation of glial cells inducing increased intracellular calcium also promotes the release of H + from glia, and it has been proposed that this may play a key role in regulating synaptic transmission (Tchernookova et al, 2018(Tchernookova et al, , 2021Choi et al, 2021). In this review and hypothesis article, we first review studies demonstrating the potency of extracellular H + as a modulator of synaptic transmission and then describe techniques used and studies conducted to show calcium-dependent extrusion of H + from glial cells activated by extracellular ATP.…”
Section: Introductionmentioning
confidence: 99%
“…The eATP regulation was involved in the inhibitory transmission of SCN synapses and mechanical pain perception as well as function recovery of astrocyte after metabolic inhibition [ 39 41 ]. The electrical activity and arginine vasopressin secretion rhythms of SCN negatively correlate with eATP level [ 27 , 32 , 42 ]; the eATP level altered extracellular H + flux in astrocytes of the hippocampus and cortex [ 43 ]. Thus, characterized by stable rhythm and wide participation in multiple system functions, eATP can be used as an important output signal of the circadian rhythm to investigate internal clock and circadian regulation.…”
Section: Introductionmentioning
confidence: 99%